Cell adhesion and twitching motility influence strong biofilm formation in Pseudomonas aeruginosa. Issue 3 (16th March 2022) - Patel, Hiral; Gajjar, Devarshi
Abstract: In the present study, biofilm formation was quantified in UTI isolates of Pseudomonas aeruginosa ( n = 22) using the crystal violet assay and was categorized into; strong ( n = 16), weak ( n = 4), and moderate ( n = 2) biofilm producers. Further experiments were done using strong ( n = 4) and weak ( n = 4) biofilm producers. Biofilm formation was greater in Luria broth followed by natural urine and artificial urine on silicone and silicone-coated latex. Cell adhesion and twitching motility were greater in strong biofilm producers. The presence of thick biofilm with an increased number of dead and total number of cells of strong biofilm producers was observed using CLSM. The concentrations of exopolymeric substances (eDNA, protein, and pel polysaccharide) were high in strong biofilm producers. FEG-SEM visualization of biofilm produced by strong biofilm producers showed more cells encased in thick biofilm matrix than weak ones. Overall results provide evidence for increased cell adhesion and twitching motility in strong biofilm producers.